2015
DOI: 10.1007/s10508-014-0464-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptoms Are Associated with Both Abstinence and Risky Sex Among Men with HIV

Abstract: Sexual abstinence is often deemed the “safest behavior” in HIV prevention, but is sometimes associated with psychological symptoms (e.g., depression) just as sexually risky behavior is. This study explored whether sexual abstinence and risky sexual behavior among men with HIV are associated with similar constellations of psychological symptoms. Prior research has not addressed this issue because abstinent people often are not included in the sample, or when data are analyzed, researchers combine abstinent peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
(86 reference statements)
1
19
0
Order By: Relevance
“…The initial sample size (N = 203) was calculated according to the formula n = 100 × (1 − p ) / p . It has been reported that 33.0–46.1% of MSM experience symptoms of depression or anxiety disorders in China [ 6 , 8 , 31 ]. To ensure an adequate sample size, the lowest prevalence rate (33%) was used as the p value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial sample size (N = 203) was calculated according to the formula n = 100 × (1 − p ) / p . It has been reported that 33.0–46.1% of MSM experience symptoms of depression or anxiety disorders in China [ 6 , 8 , 31 ]. To ensure an adequate sample size, the lowest prevalence rate (33%) was used as the p value.…”
Section: Methodsmentioning
confidence: 99%
“…The Symptom Checklist 90 (SCL-90) has been one of the most reliable psychopathological testing tools for clinical populations worldwide and is becoming one of the most popular measures with which to assess psychiatric distress in diverse cultures worldwide. SCL-90 is a self-reporting tool that has proven reliable and valid for psychological evaluation [ 29 , 30 ], including its use in HIV/AIDS studies [ 31 – 33 ]. The Chinese version of the SCL-90 has also proven reliable and valid in studies of the general population in China [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, sexually abstinent men were compared with those with high-risk sexual behavior having HIV, and the authors reported that the two groups had similar prevalence of depression, burnout, anxiety, and insomnia. [ 39 ] HIV, however, having entirely different social dynamics and established routes of sexual transmission will be different from other infectious diseases. Psychological distress and sexual abstinence have been shown to share a bi-directional relationship, as increased stress can also induce people to avoid sexual activities altogether.…”
Section: Sexual Abstinence: a Feasible Solution?mentioning
confidence: 99%
“…al., (2015) concluded in their recent review, anxiety and depressive symptoms instigate cognitive and motivational processes that may alter risk perception, can lead to cognitive distortions which can deter rational decision-making, or can lead to self-gratifying behaviors that distract from negative feelings associated with psychological symptoms. 107 High levels of stress, anxiety, and depression have been associated with both high sexual desire leading to risk (high number of sexual partners, alcohol use prior to sex, and inconsistent condom use) 108,109 and to low sexual activity that is highly risky, i.e., hypoactive sexual desire (low libido) and erectile dysfunction in combination with no condom use (to reduce likelihood of losing erections). 110113 High stress, depression, and anxiety have also been linked to high levels of acquiring sexually transmitted infections.…”
Section: Discussionmentioning
confidence: 99%